Working for Families changes: The effect on labour supply in New Zealand - Penny Mok; Joseph Mercante (New Zealand Government, The Treasury, 2014)
This paper examines the labour supply responses to the Working for Families (WfF) package of welfare reforms, which was fully implemented in 2008. The policy changes were implemented with the aim to encourage benefit recipients to participate in the labour market and to address income adequacy issues for families with children. The results presented in this paper are obtained using the behavioural microsimulation model for New Zealand, TAXMOD-B. We used the Household Economic Survey (HES) in 2008/09 to capture the full effect of the policy. It is estimated that the introduction of the new policy increases labour supply of sole parents by an average of 0.62 hours per week, but decreases labour supply of married men and women by 0.10 and 0.50 hours per week, respectively. The negative effects for married couples with dependents are about 16 and 41 times larger than for married couples without dependents, with the largest difference observed for married women. A good way of validating the results is by comparing our exante simulated effects of a policy change with the ex-post estimated effects of the policy change after it has been introduced. While it is often difficult to find policy changes which could be used to test TAXMOD-B in a similar way, the Ministry of Social Development (MSD) and Inland Revenue department (IR) have estimated labour supply effects after the WfF changes were introduced. The overall labour supply results from the simulation are in the same direction and of similar magnitudes as the ex-post results from the WfF evaluation reports. Our analysis shows that after allowing for labour supply changes, the cost of the policy change increases for couples but decreases for sole parents. These changes in labour supply are reflected in the tax revenue, family payment and benefit income changes for both subgroups. Overall, our results show that the WfF reform reduced the incidence and intensity of poverty as well as income inequality.
Keywords: C25; J22; 330; Working for Families; labour supply; discrete choice model; microsimulation; New Zealand; Familienpolitik; Arbeitsangebot; Eltern; Diskrete Entscheidung; Mikrosimulation; Neuseeland